Thermal Performance Analysis of a Low-Cost Solar Cooling System using Frugal Engineering Approach: A Case Study of Zawiya City - Hager A. Mohammed; Bashir Magtof Ghbllawi; Marzouga F. Rajab; Amyirah M. Ali; Mayzona Gemah A. (African Journal of Advanced Pure and Applied Sciences, 2026)
The escalating demand for cooling systems in hot climatic regions, coupled with increasing energy costs and environmental concerns, necessitates the development of sustainable cooling technologies. This study investigates the thermal performance of a simple solar absorption cooling system under the specific climatic conditions of Zawiya City, Libya. An experimental setup employing the Electrolux absorption refrigeration cycle was developed and tested in the Physics Laboratory at the Faculty of Science, University of Zawiya. The system utilizes an ammonia-water (NH₃-H₂O) working pair, operating without auxiliary mechanical components or active pumps, relying solely on thermal energy input. Experimental measurements were conducted at 10-minute intervals to monitor temperature variations during the cooling process. Results demonstrate a measurable temperature reduction from 26.1°C to 24.3°C, representing an approximate 1.8°C (6.9%) decrease achieved through passive solar-driven absorption mechanisms. Despite the simplicity and preliminary nature of the apparatus, the findings validate the fundamental viability of ammonia absorption cycles for cooling applications in Libya's Mediterranean climate. The study emphasizes the potential of integrating solar thermal energy as a primary heat source, replacing conventional electric heating elements, thereby reducing dependence on fossil fuels and grid electricity. These results contribute to the growing body of knowledge on renewable cooling technologies applicable to North African contexts, suggesting promising avenues for scaled implementation in residential and small commercial applications.